2017
DOI: 10.3390/nu9091007
|View full text |Cite
|
Sign up to set email alerts
|

Higher Protein Intake Does Not Improve Lean Mass Gain When Compared with RDA Recommendation in Postmenopausal Women Following Resistance Exercise Protocol: A Randomized Clinical Trial

Abstract: The aim of this study was to evaluate the effect of a higher protein intake on lean body mass (LBM) gain in postmenopausal women practicing resistance exercise and compare it to the Recommended Dietary Allowance (RDA) recommendation. Twenty-three postmenopausal women (63.2 ± 7.8 years) were randomized into two groups. The group with higher protein intake (n = 11) (HP) received a dietary plan with ~1.2 g·kg−1·day−1 of protein, while the normal protein (NP) group (n = 12) was instructed to ingest ~0.8 g·kg−1·day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…However, it is important to remember that this does not invalidate our data, because when we performed the analyses without statistical imputation the results remained the same (Table S1). In addition, the dietary and body composition data evaluating only the individuals who completed the study (without intention-to-treat analysis) can be observed in our previous study [23] and the results remained the same of the present study.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…However, it is important to remember that this does not invalidate our data, because when we performed the analyses without statistical imputation the results remained the same (Table S1). In addition, the dietary and body composition data evaluating only the individuals who completed the study (without intention-to-treat analysis) can be observed in our previous study [23] and the results remained the same of the present study.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding total fat mass, (NP—pre: 28.6 ± 2.2 vs. post: 28.2 ± 1.6 kg; and HP—pre: 27.6 ± 1.7 vs. post: 28.2 ± 1.6 kg) no changes were noted after intervention ( p = 0.902), with no differences for group ( p = 0.842) and the time × group interaction ( p = 0.680). The effect of the intervention on body composition changes evaluating only the individuals who completed the study (without intention-to-threat analysis) can be observed in our previous publication [23].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations